Assessment of nutritional status in patients with liver cirrhosis - Guerra, Thays Santana (2013)
Purpose: To assess the nutritional status of patients with liver cirrhosis and to correlate with the severity of the disease and biochemical parameters. Methods: Thirty-two patients were studied, twelve patients with liver cirrhosis by hepatitis C (37.5 %), alcohol, eleven ( 34.37 % ) and nine were studied by hepatitis C+alcohol (28.12%) , classified as Child - Pugh A (38 %), B (56%) and C (6%) with 18 ± 5 MELD . Nutritional status was assessed by BMI, Mendenhall score and Blackburn classification. Results: Malnutrition was found in 59.37 % of patients (mild in 40.62%, moderate in 15.62% and severe in 3.13%) and 37.5% overweight. The Student t-test showed no association between nutritional status and the severity of the disease assessed by Child-Pugh and MELD. Conclusion: Results showed that malnutrition is present in the patients studied, but a new scenario with an increase in the prevalence of overweight was observed regardless the hepatic impairment degree according to Child- Pugh and MELD.